Analisis Kesalahan Berbahasa Prancis Pemandu Wisata Lokal Desa Wisata Candirejo Borobudur - Endi, Ferhadius; Lestari, Dian (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research discusses the error analysis of French local tour guides in desa wisata Candirejo Borobudur. This research aims to identify and explain French language errors and the factors that cause them. This research is a qualitative descriptive study in which data collection was obtained by observation, documentation and interviews. Various forms of errors were found which included four types of language errors; omissions, additions, misformations and misorders. The two factors that cause language errors are interlingual and intralingual errors. This research is expected to contribute in improving the quality of French local tour guides in desa wisata Candirejo Borobudur.